PENERAPAN STRATEGI PEMASARAN ONLINE ICE CREAM UBI UNGU (ICU) BERDASARKAN FANPAGE FACEBOOK - Kohar Sulistyadi; Indah Rahayu Kurniasari (Universitas Sahid Surakarta, 2018)
The growing use of the internet has created an opportunity for entrepreneurs to attract consumers. The opportunity, utilized by entrepreneurs (MSMEs) to expand the reach of marketing through online advertising. Some discusses on MSMEs try to test the effectiveness of this approach on ice cream products with purple yams raw materials. Some articles describe the literature review of online advertising and how to make it work. In this article done the application of facebook fanpage as an online marketing strategy by optimizing facebook ads feature - fanpage. The end result shows a large increase in the number of consumers and on the application of e-commerce can increase the sales volume of 32% for the city of Surakarta